Grandstand simulator for dynamic human-structure interaction experiments - Comer, A; Blakeborough, A; Williams, MS (2010)
This paper describes the design, construction and use of a unique laboratory rig for the study of dynamic crowd-structure interaction in cantilever grandstands. The rig replicates a fifteen-seat section of raked grandstand, allowing laboratory tests to be performed under conditions which accurately represent those in a prototype structure. Built-in force plates enable full recording of the loads due to jumping or bobbing of each test participant, permitting detailed evaluation of group coordination levels and dynamic load factors. To investigate a wide range of dynamic structural responses, the grandstand is supported on air springs and driven using linear electric actuators. This represents a pioneering application of electric actuation technology, which is normally restricted to lower force levels and mechanical/aerospace applications. The rig also uses novel control techniques to enable the actuators to behave as spring-dashpots, allowing the rig to respond to loads imparted by the human test subjects as a dynamic system with user-defined natural frequency and damping. It is believed that this is the first time such techniques have been applied to experiments involving human participants. The rig is being used to study the factors influencing crowd coordination when jumping and bobbing on a compliant structure, and to assess acceptability limits for grandstand vibrations. Early findings suggest structural motion generated by the second harmonic of the group-jumping load does not adversely affect jumping coordination levels. This observation has significant implications for modern cantilever grandstands. © Society for Experimental Mechanics 2010.